Green Technology Adoption under Uncertainty, Increasing Returns, and Complex Adaptive Dynamics - Sanjit Dhami; Paolo Zeppini (Center for Economic Studies and ifo Institute (CESifo), 2024)
We consider firms' choices between a clean technology that benefits, and a dirty technology that harms, the environment. Green firms are more suited to the clean, and brown firms are more suited to the dirty technology. We use a model derived from complexity theory that takes account of true uncertainty and increasing returns to technology adoption. We examine theoretically, the properties of the long-run equilibrium, and provide simulated time paths of technology adoption, using plausible dynamics. The long-run outcome is an 'emergent property' of the system, and it unpredictable despite there being no external technological or preference shocks. We describe the role of taxes and subsidies in facilitating adoption of the clean technology; the conflict between optimal Pigouvian taxes and adoption of clean technologies; the optimal temporal profile of subsidies; and the desirability of an international fund to provide technology assistance to poorer countries. Finally, we extend our model to stochastic dynamics in which firms experiment with technological alternatives, and demonstrate the existence of punctuated equilibria.
Keywords: D01; D21; D90; H32; 330; technology choice; climate change; complexity; lock-in effects; increasing returns; green subsidies; public policy; Pigouvian taxes; stochastic dynamics